Positive Thinking: The Nursing Application in Mental Health Promotion to a New Normal - Naksusuk, Patrabul (Journal of The Royal Thai Army Nurses, 2021)
The newly emerging Coronavirus disease 2019 (COVID-19) has become a global pandemic with devastating consequences. The governments have imposed a number of measures to control the spread of coronavirus, which have also affected every aspect of daily life. These unprecedent measures have changed the way people live and indirectly force them to adapt to the “New Normal”. Having to adjust to this ‘New Normal’ certainly gives people a lot of stress and anxiety. Therefore, the implementation of Mental Health Promotion is the most important aspect that should be considered. The “positive thinking” is one of the effective ways which could be used to cope with stress and anxiety, as well as, to help people with the adaptation during difficult times. This paper aims to clarify roles of nurses for mental health promotion by applying the positive thinking would help people to easily/finally adjust themselves and live a happy life.